Development of Augmented Reality on Molecule Geometry to Improve Mental Models of High School Students - Amalia, Riski; Sumarni, Woro; Widiyatmoko, Arif (Universitas Negeri Semarang, 2024)
This research aims to produce augmented reality learning media for molecular form materials and improve the mental model of high school students. This research is a type of research and development using a 4D model (define, design, develop and, disseminate). The media that has been developed is validated by five validators consisting of 2 media experts and 3 material experts. In addition, feasibility tests and effectiveness tests are carried out through trials. The results of the research that have been carried out were obtained: 1) In the validity criteria obtained an average score of 94.8 in the very valid category for the material aspect and a score of 95.8 with the very valid category for the media aspect. 2) The results of the teacher's response obtained an average score of 95.3 with the very good category, while in the students' response obtained 80.1 with the good category. 3) Most students experience improved synthetic mental models. Thus, it can be concluded that augmented reality learning media molecular form material is feasible to be used to improve students' mental models. The mental model of the student increases to the synthetic category in most students who were originally in the initials category.